The role of midwifery and other international insights for maternity care in the United States: An analysis of four countries. Issue 4 (30th October 2020) - Kennedy, Holly Powell; Balaam, Marie‐Clare; Dahlen, Hannah; Declercq, Eugene; de Jonge, Ank; Downe, Soo; Ellwood, David; Homer, Caroline S. E.; Sandall, Jane; Vedam, Saraswathi; Wolfe, Ingrid
Abstract: Background: The United States (US) spends more on health care than any other high‐resource country. Despite this, their maternal and newborn outcomes are worse than all other countries with similar levels of economic development. Our purpose was to describe maternal and newborn outcomes and organization of care in four high‐resource countries (Australia, Canada, the Netherlands, and United Kingdom) with consistently better outcomes and lower health care costs, and to identify opportunities for emulation and improvement in the United States. Method: We examined resources that described health care organization and financing, provider types, birth settings, national, clinical guidelines, health care policies, surveillance data, and information for consumers. We conducted interviews with country stakeholders representing the disciplines of obstetrics, midwifery, pediatrics, neonatology, epidemiology, sociology, political science, public health, and health services. The results of the analysis were compared and contrasted with the US maternity system. Results: The four countries had lower rates of maternal mortality, low birthweight, and newborn and infant death than the United States. Five commonalities were identified as follows: (1) affordable/ accessible health care, (2) a maternity workforce that emphasized midwifery care and interprofessional collaboration, (3) respectful care and maternal autonomy, (4) evidence‐based guidelines on place of birth, and (5) national data collections systems. Conclusions: The findings reveal marked differences in the other countries compared to the United States. It is critical to consider the evidence for improved maternal and newborn outcomes with different models of care and to examine US cultural and structural failures that are leading to unacceptable and substandard maternal and infant outcomes.